RESEARCH ON STRESS AND DEFORMATION OF WR-CVT DISCONTINUOUS CONTACT STEEL ROPE UNDER TENSILE AND TORSIONAL LOADS - ZHANG Wu; WU JingLiang; LIU YiShan; SUN ShiShan; JIA YanPing (Jixie qiangdu)
In this paper, the 3-D model of discontinuous contact of 2/3 lay length steel rope is established by ProE/5.0. Finite element analysis of discontinuous contact steel rope under axial tension and torsion load was carried out in ABAQUS. The wear test of wire rope was carried out on the discontinuous contact steel wire rope damage test bench, and the distribution of wear marks on the worn steel wire surface was analyzed by optical microscope（OM）. The results show that the equivalent stress, axial stress and axial deformation are spiral distribution along the axial direction of the wire rope; on the strand section, the equivalent stress increases gradually from the core wire to the side wire, the maximum value appears in the contact area of rope groove, the experimental results show that the steel wire surface also presents elliptical wear scar, which is consistent with the simulation results.